expression of a taste-modifying protein, miraculin, in by-2 tobacco cell line (Nicotiana tabacum L. Cv Bright Yellow 2) - Hong, La Viet; Giang, Nguyen Thu; Ngoc, Pham Bich; Ha, Chu Hoang (Academia Journal of Biology, 2015)
Miraculin is a taste-modifying and low calorie protein isolated from the red berries of Richadella dulcifica, a shrub native to West Africa. In this study, a synthetic miraculin gene was designed to optimize its codon usage for BY-2 tobacco cell lines. This gene was inserted into two constructs including pBI121/HSP-pro:Mir:HSP-ter that contains HSP promoter and HSP terminator isolated from Arabidopsis thaliana for enhancing production of miraculin and pBI121/35S-pro:Mir:NOS-ter for transformation into BY-2 tobacco cell lines. The presence and expression of miraculin gene in BY-2 tobacco cell lines were verified by PCR and Western blot, respectively. It was demonstrated that transgenic BY-2 tobacco cell lines grew stably in liquid media after 4-5 times of transplant. The expression of miraculin gene in transgenic BY-2 tobacco cell lines resulted in the accumulation of miraculin protein with molecular mass of approximately 43-45 kDa. Besides, it was observed that the expression of miraculin in HSP-pro:Mir:HSP-ter transformed BY-2 tobacco cell lines is better than the expression of miraculin in 35S-pro:Mir:HSP-ter transformed ones. For the first time, miraculin recombinant protein has been expressed in BY-2 tobacco cells providing a great potential for research and production of miraculin protein at industrial scale.